Examining the General Global Competence of Students Enrolled in an International Dimension Course: An Attempt to Internationalize Undergraduate Education in a College of Agriculture - Samba Moriba; M. Craig Edwards (Journal of Human Sciences and Extension, 2015)
Many U.S. colleges and universities are concerned with how best to prepare students to become globally competent citizens. Therefore, the need existed to examine the general global competence of students enrolling in international dimension (ID) courses at Oklahoma State University. This investigation was a census study; the target population included all undergraduate students (N = 147) enrolled in three ID courses offered in the College of Agricultural Sciences and Natural Resources (CASNR) during the fall semester of the 2010–2011 academic year. General knowledge instruments were used to gather pretest and posttest data to measure differences. Although students’ post-course scores were higher than pre-course scores, their overall performance was below 60%. This difference in knowledge gain connoting general global competence was statistically significant (p < .05), but the corresponding effect size was small, which signaled little practical significance. Whether ID courses are an efficacious way of achieving substantial change in students’ general global competence remains an open question. A more appropriate method to assess change in general global competence may be writing assignments. Faculty are encouraged to improve their ID courses by infusing learning experiences that stand to enhance students’ general global competence while complementing content-specific objectives.